An exceptionally strong, ductile and impurity-tolerant austenitic stainless steel prepared by laser additive manufacturing. (15th May 2023) - Chen, Yong; Zhu, Hongmei; Zhang, Pengbo; Wang, Zhongchang; Wang, Meng; Sha, Gang; Lin, He; Ma, Jingyuan; Zhang, Zhenyuan; Song, Yong; Zheng, Pengfei; Zhou, Lihua; et al.
Abstract: The effective strategy for structural steel with excellent tolerance of impurities is to increase solidification rate to prevent the formation of segregation and intermetallic during fabrication.Carbon (C) and oxygen (O) as impurities in austenitic stainless steel are often controlled at extremely low levels to ease their detrimental effects on toughness and corrosion resistance. Hence, high-quality austenitic stainless steels are poor in impurity tolerance and moderate in strength. Here, we use laser additive manufacturing successfully engineering C, N and O with high contents as interstitial atoms coordinated with Cr in the form of short-range ordered assembly in steel, and develop an impurity-tolerant supersaturated austenitic stainless steel with an ultrahigh strength of 961±40 MPa, a good ductility (37.5 ± 3%), an enhanced corrosion resistance (0.0745 Ecorr/V) and acceptable thermal stability up to 500 °C. First-principles calculations indicate that a coordinated hexahedron C4 Cr4, as a stable unit in the austenite, can be assembled via three basic types of stacking. With the presence of N and O, N1 C6 Cr8, O1 C6 Cr7 and O1 C6 Cr8 are also stable coordination assembly units. Such short-range ordered assembly of interstitial atoms can produce significant super-saturated interstitial solid solution strengthening, which is responsible for the enhancement of tensile strength while maintaining ductility. The novel approach in engineering impurities by laser additive manufacturing may open up a new avenue in developing advanced high-impurity-tolerance steels for potential industrial applications at a low cost. Graphical abstract: Image, graphical abstract